Improving the ability of speaking in second year baccalaureate students from organizational secretariat management at “Margarita Cortes” Educational Institutionin Esmeraldas City 2014-2015 - Bolaños Valencia, Maira Alejandra (2016)
Tesis previa obtención del título de Licenciado/a en Lingüística Aplicada mención Inglés